2005
DOI: 10.2337/diabetes.54.6.1676
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Microsomal Triglyceride Transfer Protein Expression and Apolipoprotein B100 Secretion by the Citrus Flavonoid Naringenin and by Insulin Involves Activation of the Mitogen-Activated Protein Kinase Pathway in Hepatocytes

Abstract: Microsomal triglyceride transfer protein (MTP) is necessary for hepatocyte assembly and secretion of apolipoprotein (apo)B100-containing lipoproteins. The citrus flavonoid naringenin, like insulin, decreased MTP expression in HepG2 cells, resulting in inhibition of apoB100 secretion; however, the mechanism for naringenin is independent of insulin receptor substrate-1/2. Recently, it was reported that insulin decreased MTP expression in HepG2 cells via the mitogen-activated protein kinase (MAPK)/extracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
103
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 45 publications
8
103
0
Order By: Relevance
“…Our results showed for the first time that LPL expression was dramatically elevated in visceral and subcutaneous adipose tissues, and in skeletal muscle, by green tea supplementation. It has been shown that EGCG is a potent inhibitor of apoB100 secretion (40) , possibly through microsomal transfer protein inhibition, as demonstrated in vitro for other flavonoids (41) . Furthermore, EGCG promotes the accumulation of TAG in cytosolic lipid droplets, thereby diverting lipids from the assembly of VLDL to storage in the cytosol (42) .…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed for the first time that LPL expression was dramatically elevated in visceral and subcutaneous adipose tissues, and in skeletal muscle, by green tea supplementation. It has been shown that EGCG is a potent inhibitor of apoB100 secretion (40) , possibly through microsomal transfer protein inhibition, as demonstrated in vitro for other flavonoids (41) . Furthermore, EGCG promotes the accumulation of TAG in cytosolic lipid droplets, thereby diverting lipids from the assembly of VLDL to storage in the cytosol (42) .…”
Section: Discussionmentioning
confidence: 97%
“…The shaded compartments represent the compartments containing apoB radioactivity that were determined experimentally. expression (1,2). However, an extensive pulse-chase protocol coupled with multicompartmental modeling has not been used to characterize how insulin affects the kinetic movement of apoB-100 within hepatocytes.…”
mentioning
confidence: 99%
“…Activation of these two pathways results in upregulation of the LDL receptor (LDLr) and inhibition of microsomal triglyceride transfer protein (MTP), leading to the inhibition of apoB-100 secretion (1)(2)(3)(4). Exposure of cells to insulin rapidly activates intracellular signaling by tyrosine phosphorylation of the insulin receptor (IR) and insulin receptor substrate-1 (IRS-1) within 10 min (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations